Equal clinical performance of a novel point-of-care cardiac troponin I (cTnI) assay with a commonly used high-sensitivity cTnI assay - Venge, Per; Giannitsis, Evangelos (Clinica chimica acta, 2017)
Background: Efficient rule-out of acute myocardial infarction (MI) facilitates early disposition of chest pain patients in emergency departments (ED). Point-of-care (POC) cardiac troponin (cTn) may improve patient throughput. We compared the diagnostic accuracy of a novel cTnI test (Minicare cTnI, Philips), with current POC cTnI (I-Stat, Abbott) and high-sensitivity central laboratory cTnI (hs-cTnI; Architect, Abbott) assays. Methods: The clinical performance of the assays were compared in samples from 450 patients from a previous clinical evaluation of Minicare cTnI. Results: Minicare cTnI correlated with Architect hs-cTnI (r2=0.85, p<0.0001) and I-Stat cTnI (r2=0.93, p<0.0001). Areas under the receiver operating characteristics curves were 0.87-0.91 at admission (p=ns) and 0.96-0.97 3h after admission (p=ns). The negative predictive values (NPV) at admission were 95% ((92-97%, 95% CI) for Minicare cTnI and increased to 99% (97-100%) at 2-4h, and similar to Architect hs-cTnI (98%, 96-100%), but higher than I-Stat cTnI (95%, 92-97%; p<0.01). Negative likelihood ratios (LR-) after 2-4h were 0.06 (0.02-0.17, 95% CI) for Minicare cTnI, 0.11 (0.05-0.24) for Architect hs-cTnI (p=0.02) and 0.28 (0.18-0.43) for I-Stat cTnI (p<0.0001). The clinical concordances between Minicare cTnI and Architect hs-cTnI were 92% (admission) and 95% (2-4h), with lower concordances between Minicare cTnI and I-Stat cTnI (83% and 78%, respectively; p=0.007). Conclusions: The Minicare cTnI POC assay may become useful for prompt and safe ruling-out of AMI in ED patients with suspected AMI using a guideline supported 0/3h sampling protocol.
Gesehen am 24.09.2018